Catasetum tavaresii (Catasetinae), a new species from Central Brazilian Amazon - Krahl, Dayse Raiane Passos
A new Catasetum species from Brazilian Amazon, more specifically from the "Floresta Nacional de Saracá-Taquera" (State of Pará), is proposed, described and illustrated. This new taxon belongs to the subgenus Catasetum, section Isoceras, subsection Isoceras, characterized by the symmetrical and parallel antennae. It is compared with C. nhamundaense, C. garnettianum and C. barbatum, all with the same anten-nae characteristics and belonging to the "C. cristatum alliance". Among related species, C. tavaresii differs mainly in the lip structure. Additionally, we provide data on geographical distribution, habitat, phenology, flower visitors, and preliminary conservation status.